Microwave-Assisted Combustion Synthesis of Nano Iron Oxide/Iron-Coated Activated Carbon, Anthracite, Cellulose Fiber, and Silica, with Arsenic Adsorption Studies - Mallikarjuna N. Nadagouda; Darren A. Lytle (Journal of Nanotechnology, 2011)
Combustion synthesis of iron oxide/iron coated carbons such as activated carbon, anthracite, cellulose fiber, and silica is described. The reactions were carried out in alumina crucibles using a Panasonic kitchen microwave with inverter technology, and the reaction process was completed within a few minutes. The method used no additional fuel and nitrate, which is present in the precursor itself, to drive the reaction. The obtained samples were then characterized with X-ray mapping, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDS), selected area diffraction pattern (SAED), transmission electron microscopy (TEM), X-ray diffraction (XRD), and inductively coupled plasma (ICP) spectroscopy. The size of the iron oxide/iron nanoparticle-coated activated carbon, anthracite, cellulose fiber, and silica samples were found to be in the nano range (50–400 nm). The iron oxide/iron nanoparticles mostly crystallized into cubic symmetry which was confirmed by SAED. The XRD pattern indicated that iron oxide/iron nano particles existed in four major phases. That is, γ-Fe2O3, α-Fe2O3, Fe3O4, and Fe. These iron-coated activated carbon, anthracite, cellulose fiber, and silica samples were tested for arsenic adsorption through batch experiments, revealing that few samples had significant arsenic adsorption.